PENERAPAN TEKNOLOGI PAKAN SUPLEMEN UREA KAPUR CASSAVA BLOK (UKCB) UNTUK MENINGKATKAN PRODUKSI TERNAK SAPI PADA KELOMPOK TANI TERNAK TRI BUANA KARANGASEM - CAKRA, dkk., I GUSTI LANANG OKA (Buletin Udayana Mengabdi, 2014)
The community service was conducted in the cattle farmers groups “Tribuana” in Tri Eka Buana Village, Sidemen Distrik, Karangasem Regency and was aimed to improve the farmers knowlege especially the members of famers groups about the aplication of feed suplement Urea Lime Cassava Block (ULCB). The service was conducted on Saturdy on 7nd September 2013 at Tribuana Groups of farmers at banjar Pungutan, Tri Eka Buana village, and attended by 22 from 30 total members of farmers groups (73%). The methode used were direct instruction and discussion to the farmers. More than 90% members of farmers group not yet give feed suplement, only 5% members of farmers group was given feed suplement like rice brand and water washing rice before being cooked. The result of the service showed that the farmenrs’ awareness and knowlege improve to give feed suplement such as Urea Lime Cassava Block, therefore the dry matter consumption will al so improve. The nutrient requirement could fulfill and will impact to the improvement of cattle growth and production. Key words: feed suplement, cattle